The C-terminal periplasmic domain of MotB is responsible for load-dependent control of the number of stators of the bacterial flagellar motor - Castillo, David J. (Biophysics (Nagoya-shi), 2013)
The bacterial flagellar motor is made of a rotor and stators. In Salmonella it is thought that about a dozen MotA/B complexes are anchored to the peptidoglycan layer around the motor through the C-terminal peptidoglycan-binding domain of MotB to become active stators as well as proton channels. MotB consists of 309 residues, forming a single transmembrane helix (30–50), a stalk (51–100) and a C-terminal peptidoglycan-binding domain (101–309). Although the stalk is dispensable for torque generation by the motor, it is required for efficient motor performance. Residues 51 to 72 prevent premature proton leakage through the proton channel prior to stator assembly into the motor. However, the role of residues 72–100 remains unknown. Here, we analyzed the torque-speed relationship of the MotB(Δ72–100) motor. At a low speed near stall, this mutant motor produced torque at the wild-type level. Unlike the wild-type motor, however, torque dropped off drastically by slight decrease in external load and then showed a slow exponential decay over a wide range of load by its further reduction. Since it is known that the stator is a mechano-sensor and that the number of active stators changes in a load-dependent manner, we interpreted this unusual torque-speed relationship as anomaly in load-dependent control of the number of active stators. The results suggest that residues 72–100 of MotB is required for proper load-dependent control of the number of active stators around the rotor.